A 60-year drought analysis of meteorological data in the western Po River basin - E. Mombrini; S. Tamea; A. Viglione; R. Revelli (Hydrology and Earth System Sciences)
Since the start of the 21st century, increasing focus has been put on drought and its wide range of environmental and socioeconomic effects, particularly in the context of climate change. The identification of changes in drought occurrence has been done at different spatiotemporal scales and using different approaches, with results that may not be fully comparable. This study aims to analyse drought trends in the northwestern region of Italy, encompassing the Piedmont and Aosta Valley regions, characterized by diverse topography and warming rates. The analysis is carried out over the last 60 years using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) at 3- and 12-month timescales and deriving drought events at the local and regional spatial scales. By leveraging on a continuous and spatially coherent precipitation and temperature dataset, we explore the temporal and spatial variability of drought conditions and compare results obtained with different approaches.